“Jurnalistik Itu Asik” pada Pelajar Ipnu-Ippnu Ranting Desa Trikarso dan Karangtaruna Desa Trikarso - Taufik Hidayat; Muchlas Abror; Hellaisna Nur’aini Garwan; Rosita Sofyaningrum; Moch. Abdul Ghonny N. R.; Kukuh Trisnadi; Much. Ridho (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
The lack of knowledge about journalistic writing, the lack of publication of news in the village, the lack of awareness from the community about writing a news story are the reasons for implementing the thematic service for the Kebumen UMNU KKN with the theme